Structurally validated scale of measuring the link between corporate storytelling for branding & internal stakeholders' corporate brand perceptions - Brighton Nyagadza; Ernest M. Kadembo; Africa Makasi (Cogent Business & Management, 2020)
The research purpose was to assess the link between corporate storytelling for branding and internal stakeholders' corporate brand perceptions. Nomothetic quantitative explanatory research design anchored on positivist paradigm was applied. Data were collected via physical self-administered survey, resulting in 335 responses from 6 selected companies listed on the Zimbabwe Stock Exchange (ZSE), in 6 industrial sectors. Structural Equation Modelling (SEM) using AMOS version 6 software, was used to test the propositions. Results depicted that there is a positive link between corporate stories for branding elements such as corporate activities (r(335) =.15, p =.01), corporate values (r(335) =.84, p <.001), corporate associations (r(335) =.60, p <.001), corporate personality (r(335) =.90, p <.001) and emotional attachment with internal stakeholders' corporate brand perceptions (r(335) =.74, p <.001). It was recommended that the management of the selected listed companies need to consider internal stakeholders in creating convincing corporate stories for branding which yield positive perceptions. The research contributes to theory, practice and future research directions.
Keywords: M3; M31; 650; corporate brand perceptions; corporate storytelling for branding; impression management (IM); structural equation modelling (SEM); Zimbabwe Stock Exchange (ZSE)